Font Hill - Bannister, James; Brant , Marcus; Raby , Thomas; Brimicam , George
Diagram showing Major General James Bannister 2000 acres belonging to Font Hill Estate. Also land owned by the following : Marcus Brant 1000 acres, Thomas Raby two 510 acres plot, George Brimicam 430 acres. 1671.
Keywords: St. Elizabeth -- Maps; Maps